Diagnóstico diferencial entre Doença de Crohn e Hidradenite Supurativa: relato de caso - Yamashiro, Fabio da Silva [UNESP]; Romeiro, Fernando Gomes [UNESP]; Franzoni, Leticia de Campos [UNESP]; Lima, Talles Bazeia [UNESP]; Baima, Julio Pinheiro [UNESP]; Albuquerque, Idblan Carvalho de [UNESP]; Sassaki, Ligia Yukie [UNESP] (My University, 2013)
Crohn’s disease is a chronic infl ammatory bowel disease with segmental transmural infl ammation, which complicate with formation of fi stulas and abscesses. The hidradenitis suppurativa (HS) is characterized by recurrent abscesses, with a predilection for areas rich in apocrine glands such as the axillary, inguinal and perineal. The differential diagnosis between these diseases is diffi cult and may compromise treatment. Report case: C.R.M.A., 40 year-old, female, white, ileal and colonic Crohn’s disease complicated with perianal and rectovaginal fi stula for 12 years, treated with biological therapy since May 2010. In Sep/2010 presented with an abscess in the buttock D with purulent discharge refractory to the use of ciprofl oxacin and metronidazole. USG: collection of 30 cm3 in buttock D. The diagnosis was HS and the patient underwent extensive surgical removal of the affected areas (10 x 2 cm) with healing by secondary intention. Skin graft performed unsuccessfully in Dec/2010. The patient returned in jan/2011 with a new fi stula at the site of resection, consistent with Crohn’s disease. In fev/2011 underwent drainage of abscesses and placement of setons in perianal fi stulas. Currently in therapy with good biological evolution of fi stulas. The prevalence of HS varies from 0.3 to 4% of the population in general. The axilla is the region most affected and perianal lesions are associated with greater weakness. There are published reports of association between HS and Crohn’s disease sporadically and further studies are needed to assess a common pathogenesis. The differential diagnosis should be performed in all cases planning immediate treatment, avoiding complications and worsening of the patient’s quality of life.

A doença de Crohn é uma doença infl amatória intestinal crônica com infl amação transmural segmentar, que pode complicar com formação de fístulas e abscessos. A hidradenite supurativa (HS) é caracterizada por abscessos recorrentes e dolorosos, com predileção por áreas ricas em glândulas apócrinas como as regiões axilares, inguinais e perineal. O diagnóstico diferencial entre estas doenças é difícil e pode comprometer o tratamento. Relatamos o caso de C.R.M.A., 40 anos, feminina, branca, com doença de Crohn íleocolônica com fístula perianal e retovaginal há 12 anos, em terapia biológica desde maio 2010. Em setembro de 2010 apresentou abscesso em glúteo direito com saída de secreção purulenta refratária ao uso de ciprofl oxacino e metronidazol. Ultrassonografi a apresentando coleção de 30 cm3 em região glútea direita. A hipótese diagnóstica foi HS e a paciente foi submetida à ressecção cirúrgica em bloco (10 x 2 cm), com cicatrização por segunda intenção. Realizou enxerto de pele em dezembro de 2010 sem sucesso. Retornou em janeiro de 2011 com nova fístula no local da ressecção, compatível com doença de Crohn. Em fevereiro de 2011 foi submetida à drenagem dos abscessos e colocação de setons nas fístulas perianais. Atualmente em terapia biológica, com boa evolução das fístulas. A prevalência da HS varia de 0,3 a 4% da população em geral. A axila é a região mais afetada e as lesões perianais estão associadas com maior debilidade. Há relatos na literatura de associação entre a HS e a doença de Crohn de forma esporádica, e novos estudos são necessários para avaliar uma patogênese em comum. O diagnóstico diferencial deve ser realizado em todos os casos para tratamento imediato, evitando-se, assim, as complicações e a piora da qualidade de vida do doente.
Differential diagnosis between crohn’s disease and hidradenitis suppurativa: case report
Keywords: Crohn’s disease; Hidradenitis suppurativa; Perianal fistulae; Doença de Crohn; Hidradenite supurativa; Fistula perianal